PREVALENCE OF HYPERTENSION AND OTHER ASSOCIATED FACTORS AMONG INDIVIDUALS AGING 15 YEARS AND ABOVE, IN FEDERALLY ADMINISTERED TRIBAL AREAS OF PAKISTAN - Mahmood Ul Hassan; Cheragh Hussain; Shah Sawar; Muhammad Abdur Rauf; Haroon Rasheed Afridi (Khyber Medical University Journal, 2022)
OBJECTIVE: To determine the prevalence of hypertension and associated factors among age 15 years and above in federally administered tribal areas (FATA) of Pakistan.